Vibrio vulnificus rtxE Is Important for Virulence, and Its Expression Is Induced by Exposure to Host Cells - Lee, Byung Cheol (American Society for Microbiology (ASM), 2008)
Numerous secreted virulence factors have been proposed to account for the fulminating and destructive nature of Vibrio vulnificus infections. A mutant of V. vulnificus that exhibited less cytotoxicity to INT-407 human intestinal epithelial cells was screened from a library of mutants constructed by random transposon mutagenesis. A transposon-tagging method was used to identify and clone an open reading frame encoding an RTX toxin secretion ATP binding protein, RtxE, from V. vulnificus. The deduced amino acid sequence of RtxE from V. vulnificus was 91% identical to that reported from Vibrio cholerae. Functions of the rtxE gene in virulence were assessed by constructing an isogenic mutant whose rtxE gene was inactivated by allelic exchanges and by evaluating the differences between its virulence phenotype and that of the wild type in vitro and in mice. The disruption of rtxE blocked secretion of RtxA to the cell exterior and resulted in a significant reduction in cytotoxic activity against epithelial cells in vitro. Also, the intraperitoneal 50% lethal dose of the rtxE mutant was 10(4) to 10(5) times higher than that of the parental wild type, indicating that RtxE is essential for the virulence of V. vulnificus. Furthermore, the present study demonstrated that the rtxBDE genes are transcribed as one transcriptional unit under the control of a single promoter, P(rtxBDE). The activity of V. vulnificus P(rtxBDE) is induced by exposure to INT-407 cells, and the induction requires direct contact of the bacteria with the host cells.